Kontribusi konsep jarimah zina dalam pembaharuan hukum pidana Indonesia - Ishaq, Ishaq (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
This study aims to explore the contribution of the concept of adultery jarimah to the renewal of the Indonesian criminal law. The method used is the approach of the legislation. Data are taken from the interpretation of Qurâan, hadith ahkam, fikih jinayah, Draft of Criminal Code and the Criminal Code. This study shows that the definition of adultery and sanctions under Article 284 of the Criminal Code are contrary to Islamic values and indigenous national culture based on Pancasila. Therefore, it needs to be updated to include the Islamic values and indigenous national culture based on Pancasila.